Relational capital as an enhancing element of the hotel sector - Espinoza – Romero, Ashly Sthefania; Fragoso – Soto, José Carlos; Vera – Pirela, Carlos Alberto (Universidad Francisco de Paula Santander, 2023)
The purpose of this research is to analyze relational capital as an element that enhances companies in the hotel sector in Valledupar, Cesar, Colombia. The implemented methodology was a quantitative, non-experimental and cross-sectional design, counting on a population census, regarding the typology it was framed in a descriptive and field research, Epistemologically, the paradigm of this research is positivist with an inductive method. The information was collected through the application of a questionnaire prepared by the researchers called (ER-FS-0220) consisting of 33 items that evaluates relational capital through three dimensions: Dimensions of relational capital, Elements of relational capital and indicators of efficiency of relational capital. Through the analysis of the results obtained by the instrument, it was concluded that the relational capital as an element that enhances the hotel sector in the city of Valledupar is high in the results of the arithmetic means of the dimensions and indicators reviewed according to the proposed scale.